Die problematiek verbonde aan die maatskaplike hantering van die gemolesteerde kind - Spies, G. M. (Koers, 1991)
Sexual moleslation is most certainly the phenomenon that evokes most repulsion in society at large, and in the helping professions. Since this phenomenon has been exposed by various sources, it is clear at present that professional institutions or people are still not successfully geared to render a non-fragmented service to the culprit, the victim and their various families. It would appear that, when services are rendered, the various professions involved in the case are not clear with regard to their various roles. Not only does a lack of knowledge exist regarding the phenomenon dealt with, hut also regarding the legal process that is mostly involved in these cases. Almost no identified resource exists in the community which one can approach for help without the emphasis on prosecution. This may enhance the possibility that cases still be kept secret. The question may be asked whether prosecution should be the way to handle sexual molestation, a process during which the involved child cannot he fully protected. Should other forms o f help-rendering not be considered?